Presenting a Qualitative Model of Behavioral Biases in Institutional Investors' Decisions in Iran - Samii, Farzad; Farsad Amanollahi, Gholamreza; Keyghobadi, Amirreza (Management Strategies and Engineering Sciences, 2024)
The purpose of this study is to present a qualitative model of behavioral biases in institutional investors' decisions in Iran. This research is applied in terms of its goal and descriptive-analytical in nature. The research method is qualitative. The statistical population of this study includes academic experts and managers of investment companies listed on the stock exchange, selected through the snowball sampling method and theoretical saturation, with a total of 12 participants. The data collection tool is a semi-structured interview based on theoretical foundations. The data analysis was conducted using thematic analysis. The results of the qualitative section were categorized into four main themes and sub-themes. The identified cognitive and psychological factors include: "overconfidence, disposition effect, herding behavior, information bias, and mental accounting." The identified amplifying factors are: "macroeconomic decisions, information asymmetry, and information overload." The identified strategies include: "reviewing and accepting mistakes, adherence to the trading plan, and avoiding bias toward specific stocks or characteristics." The identified outcome factors are: "better performance, attracting more investors, and enhancing the efficiency of the capital market."